Pokrajinske predstave o slovenski Istri - Urbanc, Mimi (Georitem, 2011)
A cultural landscape is simultaneously a complex phenomenon and a process~it is a medium and a result of human activities and perception. This monograph is based on a postmodern view of the landscape and it understands the landscape not only as a physical phenomenon, but especially as a social and cultural document. Reading this document discloses the layers of meaning and processes that comprise it. This study examines the understanding and perception of the spatial effects from the history of Slovenian Istria in the twentieth century. It does not deal with direct changes in cultural landscape features, but rather with people's relationship to them, and so social representation theory is used to represent landscape as a complex phenomenon. The focus is on representations of the landscape and history, such as their appearance in various literary, professional, and scholarly texts. Any literature can be a source for scholarly study and can enable the creation of new geographical knowledge and awareness.